Why Employees Stay: The Indirect Path from Rewards and Work-Life Balance to Retention through Job Satisfaction - Satria, Agri Bayu; Bagis, Fatmah; Darmawan, Akhmad; Randikaparsa, Irawan (Asian Journal of Management Analytics, 2025)
With an emphasis on the mediating function of job satisfaction, this study investigates the impact of rewards and work-life balance on university employee retention. 252 staff members from three Purwokerto universities : UIN Saizu, UMP, and UNU participated in the study utilizing the purposive sampling technique, and SEM-PLS was used to analyze the data. The findings indicate that rewards have an impact on job satisfaction but do not directly raise employee retention. Work-life balance, on the other hand, affects retention both directly and indirectly through job satisfaction. Employees are more likely to be content and loyal to the company when they feel appreciated and have a healthy work-life balance. These results emphasize how crucial it is to design equitable and healthy work practices in order to increase retention. Higher education institutions are urged to create retention strategies centered on work-life balance, rewards, and job satisfaction for practical reasons. However, just three universities in a single region were included in the study. It is recommended that more institutions be included in future studies to have a more comprehensive picture.